SEJARAH KALIGRAFI ISLAM DAN KAITANNYA DENGAN TASAWUF - Nurul Hidayah Harahap; Annisa Harahap; Evi Mahyati Siregar; Ansor Hambali Hasibuan (Jurnal Shaf, 2025)
In Arabic, the art of beautiful writing is called khat, which means lines, while in English, it is known as calligraphy, which comes from the Greek, namely “kalios” which means beautiful and “graph” which means writing. Thus, calligraphy is often referred to as the art of writing in a beautiful way, especially Arabic writing, which is produced by combining certain ideas and poured on the media in accordance with applicable rules.The art of Arabic calligraphy is the art of writing using Arabic letters and has existed since the time of the Prophet Muhammad. Apart from being an art, Arabic calligraphy is also considered as knowledge and skills in imagination, because its beauty contains meaning and certain rules in its writing. In this research, a qualitative method with literature study analysis was used. Data collection techniques were carried out through literature review relevant to the topic under study, while data analysis was carried out with a descriptive approach. The results show that calligraphy art began to develop during the time of the Prophet Muhammad, as evidenced by the existence of inscriptions containing Arabic calligraphy writing. The development of calligraphy styles also occurred over time, especially during the Umayyad and Abbasid eras. During the Abbasid era, the art of calligraphy developed rapidly, and the styles that emerged during that period are still used today, especially in Islamic countries in the West.